Debating "Intrinsic Evil" - Bretzke, James T. (Horizons, 2014)
Recent US election cycles, debates about the Affordable Care Act, and a variety of so-called culture war issues have placed the term "intrinsic evil" into public discourse. This issue's roundtable affords readers the opportunity to probe deeply various dimensions of the concept, such as the pedagogical effectiveness of the term, its current use in virtue ethics, and the rhetorical effectiveness of competing moral discourses. The authors' explorations range from consideration of classical questions about the substance and circumstances of acts to a taxonomy for "intrinsic evil" to how social processes affect the discourses available to ethicists.